Looking to the future? Including children, young people and future generations in deliberations on climate action: Ireland's Citizens'Assembly 2016–2018. Issue 5 (10th December 2021) - Harris, Clodagh
Abstract : The effects of climate change are multiple and fundamental. Decisions made today may result in irreversible damage to the planet's biodiversity and ecosystems, the detrimental impacts of which will be borne by today's children, young people and those yet unborn (future generations). The use of citizens' assemblies (CAs) to tackle the issue of climate change is growing. Their remit is future focused. Yet is the future in the room? Focusing on a single case study, the recent Irish CA and Joint Oireachtas Committee on Climate Action (JOCCA) deliberations on climate action, this paper explores the extent to which children, young people and future generations were included. Its systemic analysis of the membership of both institutions, the public submissions to them and the invited expertise presented, finds that the Irish CA was 'too tightly coupled' on this issue. This may have been beneficial in terms of impact, but it came at the expense of input legitimacy and potentially intergenerational justice. Referring to international developments, it suggests how these groups may be included through enclave deliberation, institutional innovations, design experiments and future-oriented practice. .